Self-healing mechanism based on dispersed solid particles of various monomeric bismaleimides. (September 2016) - Turkenburg, D.H.; Fischer, H.R.
Graphical abstract: Abstract: In view of self-healing materials for high temperature applications we have studied the use of solid monomeric bismaleimide particles as embedded self-healing component dispersed in a host material. Below the self-healing activation temperature, bismaleimides remain inert while above it they may rapidly flow into cracks or damaged sections of the host matrix and subsequently heal it by polymerizing without use of an initiator. The polymerization of various maleimides is studied with NMR, ATR-IR, DSC and GPC, while the transport properties of the melt have been analyzed with rheology and capillary rise tests. Maleimide type and purity are the major factors that can be used to tune polymerization and transport properties. The system could be used to demonstrate extrinsic self-healing of a delaminated composite test-piece at 220 °C.